Analisis Foto Jurnalistik Dalam Konten Citizen Journalism - Adellia, Cindy (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study was to determine the denotative, connotative, and mythological meanings of photojournalism in the context of criminal news on the @infobandungraya Instagram account. The results of the study found: first, the importance of denotation in this photojournalism can be seen from the objects exposed, and the photojournalism and action of the signs that appear. Second, connotative meanings are obtained in this study through the analysis of photojournalism using six methods to obtain relevant analysis. Third, the myths that work on photo signs in this research can be read directly from the object or content of the image and the expansion of meaning in connotative meaning can be recognized so that it becomes a myth.